PERLINDUNGAN NASABAH EKONOMI SYARIAH MELALUI TRANSAKSI GADAI DALAM PERSPEKTIF FIQH MUAMALAH - Ika Atikah; Maimunah Maimunah (Hukum Islam, 2021)
Rahn (pawning) is one of the sharia economic transactions that is currently increasing in development in Indonesia. The need for funds to meet the shortcomings in everyday life makes rahn (pawn) an alternative to getting fast money loans to sharia pawnshops by pledging valuable goods as a condition of the contract (contract). In this study, using normative research with a conceptual approach and analysis approach. Primary sources of law used in this study refer to journals, proceedings, scientific papers relevant to Islamic economic law (Fiqh Muamalah). Meanwhile, secondary sources of law refer to books related to fiqh muamalah. The urgency of customer protection according to fiqh muamalah, in rahn transactions, of course, it depends on the contents of the agreement clause which is mutually agreed upon by prioritizing the principle of goodwill and the principle of justice so that both debtors and creditors have equality and equality to fulfill their rights and obligations according to the agreed agreement to avoid things that can break the contract.